الجهود التربوية للمحدثين من خلال كتب أدب الطلب: دراسة تحليلية = The educational efforts of al-Muhadithin with a special reference to the books of the etiquette of seeking knowledge: an analytical study - Fettane, Amar (2014)

(untitled)
The Muhadithun (Scholars of Prophetic Tradition) were known for their strong interest in the transmission and preservation of the Prophetic tradition. In Addition to that, their efforts towards the implementation of good educational morals, ethics and learning methodologies cannot be neglected either. The main goal of this research is to highlight this unknown aspect of their legacy and demonstrate their valuable contribution to the Islamic civilization in general and to this field of studies particularly, which is still unknown for the majority of the public. The researcher used inductive approach to uncover the educational efforts of the Muhadithin through their written legacy with special reference to the books of the etiquettes of knowledge. In addition to that, the researcher used an analytical approach to explain and demonstrate the importance and value of these works.